Dapagliflozin and Recurrent Heart Failure Hospitalizations in Heart Failure With Reduced Ejection Fraction: An Analysis of DAPA-HF. Issue 20 (18th May 2021) - Jhund, Pardeep S.; Ponikowski, Piotr; Docherty, Kieran F.; Gasparyan, Samvel B.; Böhm, Michael; Chiang, Chern-En; Desai, Akshay S.; Howlett, Jonathon; Kitakaze, Masafumi; Petrie, Mark C.; Verma, Subodh; Bengtsson, Olof; et al.
Abstract : Background: Patients with heart failure (HF) and reduced ejection fraction will experience multiple hospitalizations for heart failure during the course of their disease. We assessed the efficacy of dapagliflozin on reducing the rate of total (ie, first and repeat) hospitalizations for heart failure in the DAPA-HF trial (Dapagliflozin and Prevention of Adverse-Outcomes in Heart Failure). Methods: The total number of HF hospitalizations and cardiovascular deaths was examined by using the proportional-rates approach of Lei-Wei-Yang-Ying and a joint frailty model for each of recurrent HF hospitalizations and time to cardiovascular death. Variables associated with the risk of recurrent hospitalizations were explored in a multivariable Lei-Wei-Yang-Ying model. Results: Of 2371 participants randomly assigned to placebo, 318 experienced 469 hospitalizations for HF; of 2373 assigned to dapagliflozin, 230 patients experienced 340 admissions. In a multivariable model, factors associated with a higher risk of recurrent HF hospitalizations included higher heart rate, higher N-terminal pro-B-type natriuretic peptide, and New York Heart Association class. In the Lei-Wei-Yang-Ying model, the rate ratio for the effect of dapagliflozin on recurrent HF hospitalizations or cardiovascular death was 0.75 (95% CI, 0.65–0.88), P =0.0002. In the joint frailty model, the rate ratio for total HF hospitalizations was 0.71 (95% CI, 0.61–0.82), P <0.0001, whereas, for cardiovascular death, the hazard ratio was 0.81 (95% CI, 0.67–0.98), P =0.0282. Conclusions: Dapagliflozin reduced the risk of total (first and repeat) HF hospitalizations and cardiovascular death. Time-to-first event analysis underestimated the benefit of dapagliflozin in HF and reduced ejection fraction. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03036124.